2012
DOI: 10.4304/jltr.3.4.667-676
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Output, Input Enhancement and Collaborative Output in the Acquisition of English Passive Forms

Abstract: Abstract-This study was set up to investigate whether various Focus on Form techniques facilitate L2 grammar learning. The study involved a pre-test─post-test design with treatment and control group and attempted to examine the relative effectiveness of three focus on form techniques, i.e. input enhancement, output and collaborative output, on learning English passive forms. Forty-four Iranian learners of English were selected to participate in the study. The participants were assigned to one of the four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Furthermore, to the best of the researchers' knowledge, there has been no study conducted in Iranian EFL context dealing with the effects of elaborated input on the acquisition of English phrasal verbs. The studies conducted in this context often included other aspects of input or other areas of language (Abadikhah & Shahriyarpour, 2012;Khatib & Ghannadi, 2011;Maftoon & Sharifi, 2012;Maleki & Pazhakh, 2012;Negari & Rouhi, 2012).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to the best of the researchers' knowledge, there has been no study conducted in Iranian EFL context dealing with the effects of elaborated input on the acquisition of English phrasal verbs. The studies conducted in this context often included other aspects of input or other areas of language (Abadikhah & Shahriyarpour, 2012;Khatib & Ghannadi, 2011;Maftoon & Sharifi, 2012;Maleki & Pazhakh, 2012;Negari & Rouhi, 2012).…”
Section: The Present Studymentioning
confidence: 99%
“…A number of studies have explored the theory of input enhancement (Combs, 2009;Doughty, 2001;VanPatten, 1990) or investigated the role of input enhancement on different areas of language, especially, grammar (Lee & Huang, 2008;Kuiken & Vedder, 2002;Rott, 2007;Wong, 2012), structure ( Abadikhah & Shahriyarpour, 2012), writing (Storch, 1998, Van Gelderen, Snellings , & De Glopper, 2004, reading (Lee, 2007), and vocabulary ( Izumi, 2002;Kim, 2008;Maftoon & Sharifi Haratmeh, 2012;Rassaei, & Karbor, 2013). The role of input elaboration, however, has rarely been dealt with in promoting learners' knowledge of English (Kim, 2003), in general, and in teaching and learning English phrasal verbs, in particular.…”
Section: Effects Of Unenhanced Enhanced and Elaborated Input On Learning English Phrasal Verbs 1 Introductionmentioning
confidence: 99%
“…To make sure, for years, the effectiveness of collaborative output tasks has been investigated through various technique. In the case of collaborative output task of dictogloss, the focus has been on grammatical structures such as verb tenses, prepositions, adjective and conjunction (Abadikhah & Shahriyarpour, 2012;Collins, 2007;Kooshafar, Youhanaee & Amirian, 2012;Nasaji, 2010). Collins's (2007) study considered the impact of the mother tonguue and common developmental patterns in the domain of verb tense and aspect through dictogloss and observed that that dictogloss and interpreting contexts would be effective for verb tenses in a Japanese classroom.…”
Section: Collaborative Dictogloss Taskmentioning
confidence: 99%
“…Since the multiple choice test might provide participants with models for the production of target forms, it was administered after the fill in the blank test. Every correct response received one point and Partially correct ones were scored zero because based on the output hypothesis the correct and precise production of output can be a sign of learning (Swain, 1995, as cited in Abadikhah & Shahriyarpour, 2012). The focus of the gapped words in the fill-in the blank test was verb tenses.…”
Section: Theory and Practice In Language Studies 813mentioning
confidence: 99%